2001
DOI: 10.22452/adum.vol8no1.3
|View full text |Cite
|
Sign up to set email alerts
|

Reasons For Seeking Orthodontic Treatment A Pilot Study

Abstract: This pilot survey was conducted to determine the main reason and the motivating factors which, influence patients in seeking orthodontic treatment.115 patients aged 11-30 years old were taken from the orthodontic waiting list at the Dental Faculty, University Malaya dated December 1999 -May 2000. A structured questionnaire was designed and the survey of patients was carried out using the telephone. The desire to have a better dental appearance was the main reason (65 %) given by patients who were seeking ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…According to previous study, the main motivation factor of the patients for uptake of orthodontic treatment has been found to be an improvement in their social, personal, psychological well-being, as well as gaining of their self-confidence. In a study carried out by Abdullah et al, 16 it was found that there was a positive response by the subjects for postorthodontic treatment change in their social life and selfconfidence rather than changes in their career options. In the present study, when the mean scores of knowledge and attitude were compared based on the qualification of respondents, a significant difference was found.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to previous study, the main motivation factor of the patients for uptake of orthodontic treatment has been found to be an improvement in their social, personal, psychological well-being, as well as gaining of their self-confidence. In a study carried out by Abdullah et al, 16 it was found that there was a positive response by the subjects for postorthodontic treatment change in their social life and selfconfidence rather than changes in their career options. In the present study, when the mean scores of knowledge and attitude were compared based on the qualification of respondents, a significant difference was found.…”
Section: Discussionmentioning
confidence: 97%
“…They simulated it to the wearing of optical glasses for eyesight problems. 16 In yet another study conducted in Kingdom of Saudi Arabia, it was found that patients were more apprehensive for pain and discomfort in wearing the braces than its effect on esthetics. They were more concerned about the discomfort they might face during the archwire activation.…”
Section: Discussionmentioning
confidence: 98%
“…The findings from this research will add on to the pool of knowledge gathered from other studies that have been carried out in Malaysia. 9,[18][19][20] Malaysian population is multi-races, which consist of Malay, Chinese, Indian and others. The 2010 Population and Housing Census of Malaysia (Census 2010) reported that Pahang, with 1.5 million in population consist of 79% Bumiputra, 16.2% Chinese and 4.4% Indian.…”
Section: Discussionmentioning
confidence: 99%
“…Perawatan ortodonti umumnya dilakukan karena alasan psikologis, yaitu untuk meningkatkan penampilan gigi dan estetik. 1 Perawatan ortodonti adalah salah satu jenis perawatan di bidang kedokteran gigi yang bertujuan mendapatkan penampilan dentofasial yang memuaskan secara estetik yaitu dengan menghilangkan susunan gigi yang berjejal, mengoreksi penyimpangan rotasional dari gigigeligi, mengoreksi hubungan antar insisal serta menciptakan hubungan oklusi yang baik. 2 Perawatan ortodonti harus dapat mengoreksi maloklusi dan meningkatkan kesehatan gigi dan mulut.…”
Section: Pendahuluanunclassified